Optimizing mass production of Trichoderma asperelloides by submerged liquid fermentation and its antagonism against Sclerotinia sclerotiorum - Rezende, Larissa Castro de; Andrade Carvalho, Andre Luiz de; Costa, Lucio Bertoldo [UNESP]; Halfeld-Vieira, Bernardo De Almeida; Silva, Lucas Guedes [UNESP]; Pinto, Zayame Vegette [UNESP]; Boechat Morandi, Marcelo Augusto; Vasconcelos de Medeiros, Flavio Henrique; Mascarin, Gabriel Moura; Bettiol, Wagner (Springer, 2020)
Commercial products based on Trichoderma are obtained mainly from solid-state fermentation. Submerged liquid fermentation is the most appropriate method compared to the solid medium for large-scale production of Trichoderma spp. The present study aimed to optimize the combination of key variables that influence the liquid fermentation process of Trichoderma asperelloides LQC-96 for conidial production coupled with its efficiency in the control of Sclerotinia sclerotiorum. In addition, we verified whether the optimized culture conditions can be used for the conidial production of Trichoderma erinaceum T-12 and T-18 and Trichoderma harzianum T-15. Fermentation studies were performed in shake flasks following a planned experimental design to reduce the number of tests and consumable costs. The effect of temperature, pH, photoperiod, carbon:nitrogen ratio and water activity on conidial production were assessed, which of pH was the only meaningful factor contributing to increased conidial production of T. asperelloides LQC-96. From the five variables studied initially, pH and C:N ratio were further used in the second design (rotational central composite design-RCCD). Hence, the best conditions for the production of T. asperelloides LQC-96 conidia by liquid fermentation consisted of initial pH of 3.5, C:N ratio of 200:1 at 30 degrees C, without glycerol, and under 24 h photoperiod. The highest conidial concentration was observed after seven days of fermentation. Under these optimal conditions, T. erinaceum T-12 and T-18, and T. harzianum T-15 were also cultivated, but only LQC-96 efficiently parasitized S. sclerotiorum, precluding sclerotium myceliogenic germination. Our findings propose optimal fermentation conditions that maximize conidial production of T. asperelloides as a potential biofungicide against S. sclerotiorum.
Keywords: Biofungicides; Bioreactor; Design of experiments; Submerged spores; Shite mold